2016
DOI: 10.1016/j.enbuild.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of real-time context-aware feedback on occupants’ heating behaviour and thermal adaptation

Abstract: Studies have shown that building energy demand in identical dwellings could vary by a factor of three. Differences in occupant behaviour-i.e. purchase, operation and maintenance-have been implicated as a strong source of these differences. The literature suggests that feedback on energy use to building occupants-particularly real-time feedback-can be used to prompt lower operation-related energy behaviours. This is particularly true for thermal demand which, in cold countries, accounts for four times as much e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
1
20
0
2
Order By: Relevance
“…This is in accordance with previous research which showed that warmth is closely related to comfort [66]. However, is has also been demonstrated that temperature adjustments do not necessarily impact on thermal comfort [45].…”
Section: Reported Changes In Practicesupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with previous research which showed that warmth is closely related to comfort [66]. However, is has also been demonstrated that temperature adjustments do not necessarily impact on thermal comfort [45].…”
Section: Reported Changes In Practicesupporting
confidence: 93%
“…coaching, audits, community courses), goal setting, prompts, comparison with other households, targeted information provision and real-time feedback delivery through ICT. The effectiveness of feedback systems to reduce long term resource use is unclear; some researchers have shown that they generate positive outcomes [43][44][45][46] while others believe them to only be relevant in the short term [7,11,12]. Nevertheless, individual response varies with approach and therefore mixing technical and social approaches may lead to improved consumer engagement enabling change [47].…”
Section: Behaviour Change Intervention Designmentioning
confidence: 99%
“…To address RQ1 and the latter half of RQ2, continuous on-site monitoring of T a , RH, and CO 2 was conducted in the investigated buildings (Table 5) (Elnaklah 2020). Continuous measurements were undertaken using Raspberry-Pi-based sensors that have undergone rigorous testing and calibration, making them suitable for obtaining time series with good accuracy (Vellei et al 2016;Lovett et al 2016). Monitored buildings were provided with 83 Raspberry-Pi to monitor air temperature and relative humidity, and 21 Raspberry-Pi to monitor CO2 (Figure 4).…”
Section: Objective Measurementsmentioning
confidence: 99%
“…The study was carried out during transitional periods from dry to rainy season. Every period will create occupants' thermal responses [8]. The periods were selected based on the belief that the periods will create unique responses.…”
Section: Hermawan Eddy Prianto Erni Setyowatimentioning
confidence: 99%